Mampukah Financial Performance Memoderasi Defered Tax dan Ukuran Perusahaan terhadap Penghindaran Pajak - Supriadi, Adi (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
This study addresses the critical need to understand how financial performance influences the relationship between deferred tax, company size, and tax avoidance, particularly within the manufacturing sector of the Indonesia Stock Exchange. By employing a quantitative research design with an associative approach, this research utilizes secondary data collected from selected manufacturing firms over a four-year period. The panel data regression analysis, conducted using Eviews version 12, allows for an in-depth examination of these dynamics. Findings reveal that financial performance plays a significant moderating role in the impact of deferred tax on tax avoidance, suggesting that stronger financial health can influence corporate tax strategies related to deferred tax. However, financial performance does not appear to alter the relationship between company size and tax avoidance, indicating that size-related tax behaviors operate independently of a firm’s financial condition. These insights provide valuable implications for policymakers and corporate managers by highlighting the importance of financial performance in shaping tax practices related to deferred tax, while also suggesting that company size remains a consistent factor regardless of financial strength. Understanding these nuances aids in designing more effective regulatory frameworks and corporate governance policies aimed at minimizing tax avoidance behaviors in emerging markets. This study contributes to the broader discussion on corporate taxation by clarifying the conditional effects of financial metrics on tax-related decisions.